CARACTERIZAÇÃO DE VIDROS TELURITOS DOPADOS COM NANOPARTICULAS DE Ag@PVP E AgNO3@PVP SEM E CO-DOPADAS COM Tb3+ - GOMES, Leonardo Moreira e Silva; CAPIOTTO, Adriana do Carmo; LIMA, Sandro Marcio; ARRUDA, Gilberto José (ANAIS DO ENIC, 2023)
-